THE DEVELOPMENT OF CONSTRUCTIVE INTERACTION SKILL AS A COMPONENT OF SOCIAL SUCCESS OF JUNIOR PUPIL - Mytnyk, Alexandr; Matvienko, Olena; Guraliuk, Andrii; Mykhalchuk, Nataliia; Ivashkevych, Ernest (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article proves that in order to achieve success in a person's society, it is important to be not only intellectually developed, but also to be able to work effectively in a team. The analysis of a scientific literature shows that there is a lack of research aimed at the purposeful development of students' ability to interact constructively with others. The purpose of the article is to reveal the theoretical and practical foundations for the development of the ability to constructively interact with others in primary school students. The following methods were used: theoretical analysis of a scientific literature on the problem of research, modeling, in order to describe the technique of constructing tasks for joint activities; empirical methods: diagnostic techniques, psychological and pedagogical experiment; methodology for building teaching as a holistic creative process.The article describes the essence of constructive interaction between the subjects of the educational process, presents the psychological and pedagogical conditions for the development of students of primary school age, the ability to constructively interact with others, namely: the introduction of the course "Logic" in the educational process of primary school in grades from  2 to4, tasks, related to the content of the course "Logic", in the lessons on the disciplines of the humanities and natural-mathematical cycles; the use of interactive teaching methods in the educational process; creation and implementation of tasks for joint educational activities, providing for the "I - inclusion" of everyone in joint work. A system of tasks related to the content of the course "Logic" is presented, examples of tasks of a combined nature are given and the process of working on them is described. The creation of tasks for joint educational activities in large and small groups by means of ICT is described, examples of such tasks are given, the process of working on such tasks is described.With the help of the introduction of certain diagnostic techniques and the organization of experimental research at the all-Ukrainian level, the positive dynamics of the development of students' ability to interact constructively with others and, as a consequence, the effectiveness of the named psychological and pedagogical conditions for the development of the presented skill have been proved.